FOREST CONSERVATION PARTNERSHIPS FOR SUSTAINABLE COMMUNITY DEVELOPMENT IN LAMPUNG PROTECTED AREAS - Denny Saputra Pratama; Indra Gumay Febryano; Eny Puspasari; Christine Wulandari (Jurnal Belantara, 2026)
The government has implemented the Conservation Partnership scheme as an effort to resolve land conflicts in conservation areas. This study aims to analyze the implementation of the Conservation Partnership in Gapoktanhut SHK Lestari in Wan Abdul Rachman Forest Park. The research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and document analysis. The results show that the implementation of the Conservation Partnership in Cilimus Village has changed the relationship between the local community and the forest park management from land tenure conflict to a cooperative relationship through the recognition of land management access. The partnership involves the direct participation of the community in land management, supported by the institutional role of Forest Farmer Groups and the application of an agroforestry system, with 21 Forest Farmer Groups holding access permits, consisting of 2 KTH Main Class and 19 KTH Intermediate Class, involving 512 households and a total management area of approximately 790.94 ha. Community development is carried out through the use of non-timber forest products as sources of livelihood, including post-harvest processing activities largely undertaken by women’s groups, as well as the involvement of group members in forest patrols and conservation activities. On the other hand, the implementation of the partnership still faces several challenges, including dependence on middlemen for product marketing, low involvement of younger generations in farming activities, land area adjustments within permit arrangements, and the administrative burden of economic reporting experienced by some elderly group members.